The short- to medium-term predictive validity of the HoNOS-Secure on violence in a medium-secure forensic psychiatric ward in New Zealand - Lin, Xiaohui I. (The journal of forensic psychiatry & psychology, 2023)
Violence risk prediction in forensic mental health care settings is important in facilitating its management. Although not specifically developed for risk assessment, previous studies have demonstrated that the Health of the Nation Outcome Scales-Secure (HoNOS-secure) and its predecessor may have some predictive validity for violence. This retrospective cohort study examines the predictive validity of HoNOS-secure scores rated on admission in a medium-secure forensic psychiatric ward in New Zealand for inpatient violence in the short- to medium-term at 30 and 90 days respectively. A sample size of 33 eligible admissions was obtained within the study period (2005–2017), and incident reports were rated by two independent clinicians for the occurrence and level of inpatient violence. Poisson, negative binomial and Cox regression analyses were used to investigate HoNOS-secure predictivity for the occurrence of inpatient violence, number of violent events, and time to the first violent event respectively. Although the HoNOS-secure total and subscale scores were not found to be significant predictors, post hoc analysis at the item level demonstrated association of various items with violence. Future studies could consider pooling data from multiple study sites, extending follow-up periods and adopting a prospective design.